CAPABILITIES OF THE SERVICE OF MANPOWER AND TRANSMIGRATION IN REDUCING THE UNEMPLOYMENT RATE IN SUKABUMI DISTRICT - Saskia Zahra; Rizki Hegia Sampurna; Dine Meigawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This research is entitled